Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

La recherche au profit d’un meilleur accès aux services de santé en français [numéro thématique] - Dupuis-Blanchard, Suzanne; Vézina, Sylvain (Minorités linguistiques et société / LinguisticnMinorities and Society, 2015)

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.